Les joies de Lesbos : un guide tendre et libéré des plaisirs et des problèmes de la vie lesbienne - Sisley, Emily L.; Harris, Bertha (Paris : JC Lattès, 1979)
Fonds Suzan Daniel (FSD)
Frans
Monografie